Pengaruh Partisipasi Anggaran, Kejelasan Sasaran Anggaran, Desentralisasi, dan Akuntabilitas Publik terhadap Kinerja Manajerial - Febdwi Suryani; Pujiono Pujiono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to analyze the effect of budget participation, clarity of budget targets, decentralization, and public accountability on managerial performance. Population of this research was 31 Regional Apparatus Organizations (OPD) in Pekanbaru City, there are officials at the head level, heads of offices / sections / fields / sub-services, secretaries, and heads of subsections / sub-sectors / sections of the secretariat, agencies, and officed. The data was collected by distributing questionnaires to 124 respondents, while the questionnaires that could be used were only 89 respondents. Data were analyzed using multiple linear analysis. The results of the analysis found that there is a significant influence between budget participation and managerial performance, there is no significant influence between the clarity of budget targets on managerial performance, there is a significant influence between decentralization and managerial performance, and there is no significant influence between public accountability on managerial performance. The result of testing the coefficient of determination of the hypothesis in this study was 50.3%, while the remaining 49.7% was influenced by other variables not included in this study. The value of t table in this study is 1.662, while the t value of the first hypothesis is -17,166> - 1,668, the second hypothesis is 20,107> 1,668, the third hypothesis is -2,481> -1,668, and the fourth hypothesis is -2,248> -1,668. Keywords: Managerial Performance, Budget Participation, Clarity of Budget Objectives, Decentralization, and Public Accountability.